Managerial shareholdings and performance of listed companies in Malaysia / Najah Mokhtar ... [et al.] - Mokhtar, Najah; Ali, Syukriah; Abu Hassan, Anita (2013)
The issue of corporate governance in Malaysia emerged in 1997 and fast became a very important topic . Corporate governance is, to a large extent a set of mechanisms through which outside investors protect themselves against expropriation by insiders. Managerial and institutional ownership are the corporate governance mechanisms used in corporations to overcome agency problem between manager-shareholders. However greater used of this mechanism will not necessarily ensure that corporations could eliminate the problem of wealth expropriation by managers, whereas it may be create another agency problem . The controlling shareholders, either individuals/families , or institutional/corporations, are in the position to expropriate minority interest using their dominant voting right This suggests that large ownership will adversely affect corporate value ; increasing ownership has negative relation with firm performance . An issue arise here is what is the effect of institutional and managerial ownership on firm performance of companies in Malaysia?